(untitled) (Eurasian Medical Research Periodical, 2023)
Neurosis-like states are a group of neuropsychiatric diseases that resemble neuroses in their symptoms, but the occurrence of which is not caused by a stress factor or psychological causes. A neurosis-like syndrome is manifested by such symptoms as lethargy, increased fatigue, distracted attention, general malaise , irritability , irascibility, anger , anxiety, anxiety, and fears. A neurosis-like state is caused not by the very presence of the above diseases, but by the fact that, arising and developing, they lead to disturbances in the functioning of certain brain structures (hypothalamiclimbic), which in turn leads to a disorder in the neurodynamics of the cerebral cortex.